Practically Speaking - Rodriguez, Elisabeth; Moreno, María Antonia García (Qualitative and Quantitative Methods in Libraries; Vol 7 No 4 (2018): December 2018 Issue, 2019)
International faculty exchanges offer academics the opportunity to learn from one another, culturally and scholarly. Deciding to participate in a partnership requires a substantial amount of time, planning, trust, and communication. However, the investment is most rewarding and offers the opportunity to develop collaborations and friendships, as well as to develop new scholarship. Using reflective questions, this paper is arranged to offer both those seeking to be future visiting scholars, and those considered to be faculty hosts, practical advice on each stage of the planning process.